2019
DOI: 10.1021/acs.langmuir.9b02058
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Formation and Properties of Trapped Nanobubbles and Surface Nanobubbles by Spontaneous and Temperature Difference Methods

Abstract: Trapped nanobubbles are gas domains trapped at nanopits on the solid−liquid interface. This is different from surface nanobubbles that usually form at the smooth surface. Herein, both trapped nanobubbles and surface nanobubbles formed on the nanopitted polystyrene film were studied by a spontaneous formation method and a temperature difference method. Trapped nanobubbles behave more flexibly than surface nanobubbles under different scanning loads. The nanopits under trapped nanobubbles appear after being subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 52 publications
3
17
0
Order By: Relevance
“…During trapped nanobubble nucleation, the triple-phase contact line will first experience a change from the bottom of the nanopit to pin at the pit mouth (form 1); after reaching the stage of pinning at the pit mouth (form 2), the trapped nanobubble will experience an unstable state in the course of expansion, and then, the pinned contact line begins to extend around the pit mouth and at last reach form 3. In our experiments, the observed trapped nanobubbles are usually in form 3, which has also been observed in our recent experimental study . This means that the trapped nanobubbles have extended around the pit mouth.…”
Section: Results and Discussionmentioning
confidence: 99%
“…During trapped nanobubble nucleation, the triple-phase contact line will first experience a change from the bottom of the nanopit to pin at the pit mouth (form 1); after reaching the stage of pinning at the pit mouth (form 2), the trapped nanobubble will experience an unstable state in the course of expansion, and then, the pinned contact line begins to extend around the pit mouth and at last reach form 3. In our experiments, the observed trapped nanobubbles are usually in form 3, which has also been observed in our recent experimental study . This means that the trapped nanobubbles have extended around the pit mouth.…”
Section: Results and Discussionmentioning
confidence: 99%
“…43−46 The process of nanobubble formation on nanopits has been investigated in one of our recent works. 38,45 It is found that the size of nanopits has an important influence on the entrapped nanobubbles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…According to the crevice model proposed by Atchley and Prosperetti, the gas molecules near the liquid–solid interface can be entrapped in crevices or pits and then grow by gas expansion or by gas diffusion and at last protrude out and nucleate surface nanobubbles. This indicates that surface structure is also an important factor for bubble nucleation. The process of nanobubble formation on nanopits has been investigated in one of our recent works. , It is found that the size of nanopits has an important influence on the entrapped nanobubbles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This solution injection is considered the start of the experiment (i.e., t = 0). The sudden temperature change in the solution near the surface induces initial gas bubble nucleation due to the gas solubility decrease associated with temperature . After 10 min, solution 2 with bulk gas solubility S gas,2 , was injected also at 50 μL min –1 into the flow cell at 50 °C.…”
Section: Methodsmentioning
confidence: 99%